Explanation of the Midwifery Lecturers' Experiences of the Challenges in an Undergraduate Midwifery Program: A Phenomenological Study - Farzaneh Ashrafinia; Behnaz Bagherian; Masumeh Ghazanfarpour; Ommolbanin Heydari (Kerman University of Medical Sciences, 2022)
Background: Continuing professional development is an essential component of educational organizations in health care systems around the world. Such development has received attention in recent years with a broader perspective in the field of midwifery. Accordingly, the internal evaluation approach used to identify educational strengths and weaknesses can pave the way for a more purposeful future. This study aims to explore the experiences of midwifery lecturers of the challenges of the undergraduate educational program. Methods: This study employed a qualitative phenomenological approach using the data collected through individual interviews with midwifery lecturers at Kerman University of Medical Sciences, and analyzed from October to December 2020 for three months. To this end, eight semi-structured and in-depth interviews were conducted with eight midwifery lecturers who were selected using purposive sampling. The sampling was continued until the data were saturated. All interviews were analyzed after transcription using Colaizzi's seven-step approach. Results: Analysis of the data revealed seven categories including inefficient policymaking, lack of motivation and confidence, lack of educational equipment and facilities (network of shortcomings), challenges of the curriculum and teaching methods, poor clinical conditions, disinterest in research activities, and inadequate academic output. Each category was divided into several subcategories. Conclusion: Along with achieving the fifth Millennium Development Goals, it is necessary to improve the quality of midwifery education. The challenges pointed out by midwifery lecturers highlight the need to make changes in the clinical and educational environment of the midwifery department to improve clinical skills and achieve the goals of the educational program following international education standards and consequently train skilled and educated midwifery staff.